Investigative Study on Effect of Emotional Intelligence on Job Satisfaction and Performance - Shahu, Rashmi (Prabandhan: Indian Journal of Management, 2010)
Emotional intelligence is a very critical aspect in the present business scenario. The present study aims to find the effect of emotional intelligence on job satisfaction and performance of the employees. The study can help the business organizations to understand their human resource and pay attention to improve their performance by concentrating on these psychological problems. The study consists of employees from Manganese Ore India Ltd. (MOIL).The sample size was 70 considering variables like age, education and job rank. The result show that poor score in emotional intelligence leads to poor job satisfaction and ultimately results in poor performance.